The health education based on family support toward self-care AVF access and life quality of patient with hemodialysis - Nafisah, Siti; Kristiyawati, Sri Puguh; Mubarak, Zaky (University of Muhammadiyah Malang, 2023)
Background: According to a report by the Indonesian Renal Registry (RII) in 2017, the number of patients with chronic kidney disease increased drastically. It shows more patients who may have hemodialysis. Patients with hemodialysis use AVF Access to ease the therapy process. Education based on family support is needed to help patients in self-care, using AVF Access, and improving the quality of patients. Purpose: This research aims to know the impact of education based on family support toward self-care and the life quality of patients with hemodialysis. Methods: The methodology of research used is total sampling. There are 22 samples of patients with hemodialysis with AVF Access that fulfill inclusive criteria (living with family, having components awareness, and doing regular hemodialysis twice a week). The instruments to collect data are questionnaires of self-treatment with ACF Access and KDQL SFTM-36. The data is analyzed with the validating technique of the T Dependent Test with a significance level of 0,05. Result: The result shows that most respondents have good self-treatment for 14 patients (63,6%), proven by p-value = 0,000. The life quality of most respondents is good, proven by p-value = 0,00. Conclusion: In conclusion, there is a significant, substantial, and one-way correlation between education based on family support toward self-care AVF Access and the life quality of patients with hemodialysis. Family is obliged to give more support to patients with hemodialysis to do self-care well so the life quality of patients may improve.